BIBI HALEEMA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Rokitansky-Küster (RK) syndrome is a disorder that causes the vagina and uterus to be underdeveloped or absent. Without a uterus, affected women do not have menstrual periods. Often, the first noticeable sign of MRKH syndrome is that menstruation does not begin by age 15 (primary amenorrhea). Girls and women with MRKH syndrome have a 46,XX chromosome pattern. They have normal external genitalia and functioning ovaries. They also have normal breast and pubic hair development. Although women with this condition are unable to carry a pregnancy, they may be able to have children with the help of assisted reproductive technologies or a uterus transplant.